Facile conversion of coal tar to orange fluorescent carbon quantum dots and their composite encapsulated by liposomes for bioimaging. (2nd November 2017) - Geng, Bijiang; Yang, Dewen; Zheng, Fengfeng; Zhang, Chen; Zhan, Jing; Li, Zhen; Pan, Dengyu; Wang, Liang
Abstract : Our work has provided a way for the conversion of low-value coal tar into high-value fluorescent carbon materials. Abstract : Carbon quantum dots (CQDs) are considered ideal fluorescent probes owing to their excellent optical properties and low cytotoxicity. We report a low-cost solvothermal method to synthesize orange fluorescent CQDs from coal tar. The as-fabricated CQDs exhibit bright and stable photoluminescence with long wavelength emission at 605 nm. To improve the biocompatibility of the oil-soluble CQDs, we chose liposomes as a carrier. After being encapsulated by liposomes, the CQDs become water-soluble and show a redshift of fluorescence to 640 nm. The in vitro and in vivo imaging application of the liposome-CQDs is demonstrated. Our work has provided a way for the conversion of low-value coal tar into high-value fluorescent carbon materials.